Oxidative kinetic resolution of alcohols using chiral Mn-salen complex immobilized onto ionic liquid modified silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
The supported ionic liquid strategy has been applied for the immobilization of chiral Mn(III) salen complex onto ionic liquid modified silica. Chiral Mn(III) salen complex was immobilized over silica through a thin film of covalently anchored imidazolium ionic liquid. These catalysts were characterized by N(2) sorption, XRD, MR, DRUV-vis, and elemental analysis. The results showed that the chiral Mn(III) salen complex could be successfully immobilized onto the modified mesoporous materials and that the long-range mesoporous ordering of parent supports was maintained after the immobilization. The immobilized catalyst provided good enantioselectivity and activity in the heterogeneous catalysis of the oxidative kinetic resolution of secondary alcohol and can be recovered and recycled for four times without obvious loss of enantioselectivity and activity. Oxidative kinetic resolutions of meso-diols, hydroxyl ester and primary alcohol were also studied using this catalyst system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mesoporous silica; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Ordered mesoporous silica as supports in the heterogeneous asymmetric catalysis - Sahoo, Suman; Bordoloi, Ankur; Halligudi, Shivaraj B. (Catalysis Surveys from Asia, 2011)
Enantioselective synthesis of organic compounds has been studied by homogeneous catalysts for several years. However, these catalysts have yet to make a significant impact on industrial scales for fine chemical synthesis. A primary reason is the designing of a homogeneous asymmetric catalyst, which requires relatively bulky ligands and catalyst recovery and recycling often causes problems. One of the convincing ways to overcome this problem is to immobilise the asymmetric catalyst onto a solid support and the resulting heterogeneous asymmetric catalyst system can, in principle, be readily re-used. A large number of supports such as inorganic oxides including zeolites, alumina, zirconia, silica and organic polymers have been employed as supports in heterogeneous asymmetric catalysis. Therefore, in this review article we have summarized the work done by us in our laboratory on the immobilization of chiral transition metal complexes such as Ru, Ir, Mn and Ti onto ordered mesoporous silica and its asymmetric catalysis. All these immobilized catalysts were well characterized by different physicochemical techniques to confirm the structural retention of the support as well as the active metal complex after immobilization. This report includes our asymmetric catalytic investigations in enantioselective reactions such as hydrogenation of ketones, olefins, oxidation of sulfides and oxidative kinetic resolution of alcohols and sulfoxides through immobilized heterogeneous catalyst systems.
Keywords: Enantioselective hydrogenation; Enantioselective oxidation; Immobilization; Mesoporous silica; Oxidative kinetic resolution